PENGARUH ARUS KAS OPERASIONAL DAN TOTAL ASET TERHADAP ROE DI CV GLOBAL PERMATA SINERGI PERIODE 2019-2021 - Winda Fauziah; Aida Wijaya (Jurnal Riset Akuntansi Politala, 2023)
In March 2020, the Covid-19 pandemic that hit Indonesia resulted in many business activities dropping, including the company CV Global Permata Sinergi. Based on the financial statements, especially operational cash flow, there was a drastic decline, which was down almost 75% from the previous year. However, in 2021, cash flow will increase again, even though the pandemic condition has not ended. Apart from operational cash flow, this study also examines total assets to see whether the size of assets affects the company's income, which is proxied by ROE. This study is conducted based on financial reports taken from 2019 to 2021 at CV Global Permata Sinergi, in which a sample of 36 data was selected. The results of this study indicate that operational cash flow and total assets have a significant positive effect on the return on equity at CV Global Permata Sinergi.